Trio Album for violin, violoncello & piano, vol. III Violin part - CUI, Cesar [et.al] (The Boston Music Co.)
FernientenBoleronAndante MelodiquenA DoubtnVivacenSerenadenSpanish dancenNarcissiusnStandchennWaltz